Knowledge and practice of ethics among postgraduates in a public sector tertiary care hospital - Sahlish Kumar; Iqra Ismail; Komal Noorani; Fatima Ashraf Ganatra; Insiya Hashim; Sara Maratib Ali; Abu Talib (Journal of the Pakistan Medical Association, 2022)
Objective: To explore the present state of competency in clinical ethics among postgraduate trainees in a tertiary care hospital. Methods: The interview-based cross-sectional study was conducted at the Civil Hospital, Karachi, from September 2018 to March 2019, and comprised postgraduate trainees of either gender in any year of the training program across all specialties. Data was collected using self-reported questionnaire seeking opinion about present working conditions regarding clinical ethical issues on the hospital ground and problems they face from day to day. Data was analysed using SPSS 23. Results: Of the 153 subjects, 96(62.7%) were females, 73(47.7%) were from Medicine and allied disciplines, and 80(52.3%) were from Surgery and allied disciplines. The primary source of their clinical ethics’ understanding was derived from their workplace [116(75.82%)]. While only 104 (68%) of the subjects knew about the Hippocratic Oath’s contents, less than 10% knew about Nuremberg Code and Helsinki declaration. They mainly relied on their seniors at work for guidance on ethical issues [108 (70.59%)]. Overall, the subjects lacked basic knowledge of medical ethics and failed to practise ethical conduct during their training. Conclusions: The knowledge of medical ethics was found to be unsatisfactory among doctors, and timely intervention was needed to improve the situation. Key Words: Clinical ethics, Postgraduate education, Knowledge, Practices, Pakistan.